The Impact of Financial Risk on Leverage, Profitability, and Firm Value in Indonesian Companies - Diantara, Ega Hendri; Budiarto, Dekeng Setyo (InFestasi, 2025)
It is common knowledge that the COVID-19 pandemic has significantly impacted the performance of companies worldwide, including Indonesia. The impact of the pandemic has resulted in two pressures, both positive with increasing profits and negative with the closure of companies. This study will examine the differences in profitability ratios, leverage, and firm value based on the impact of risk after COVID-19. This study was conducted on all companies (except the banking sector) listed on the Indonesia Stock Exchange (IDX). This study uses a purposive sampling technique, so 403 companies were obtained with 797 observations. The data in this study is divided into 2 categories, namely, first, companies that are positively impacted, and second, companies that are negatively impacted by the pandemic. Hypothesis testing uses Mann-Whitney because the data distribution is not normal. The study results show differences in the Long-Term Debt to Equity Ratio (LTDtER) based on the impact of company risk. Furthermore, the test results show that there is no difference in the impact of financial company risk on ROE and Tobin's Q. The novelty of this research is that it provides a methodological contribution that analyzes the impact of financial risk before the pandemic and then compares financial data after the pandemic. The results of this study provide recommendations to stakeholders on how to use the right strategy when investing in companies that go public in Indonesia. This study provides theoretical implications by proving that the impact of financial company risk will result in an increase in long-term debt for the company.